2016 International Conference on Advanced Materials for Science and Engineering (ICAMSE) 2016
DOI: 10.1109/icamse.2016.7840359
|View full text |Cite
|
Sign up to set email alerts
|

An investigation into the use of virtual reality technology for passenger infotainment in a vehicular environment

Abstract: The paper presents a prototype Head Up Display interface which acts as an interactive infotainment system for rear seat younger passengers, aiming to minimize driver distraction. The interface employs an Augmented Reality medium that utilizes the external scenery as a background for two platform games explicitly designed for this system. Additionally, the system provides AR embedded information on major en route landmarks, navigational data, and local news amongst other infotainment options. The proposed desig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 7 publications
0
12
0
Order By: Relevance
“…Previous studies have demonstrated the impact of rear-seat passengers' activity on driver distraction [16,17], but this issue is amplified, in most ES situations, as the codriver, normally assisting in navigation, is often required to aid a patient and thus cannot offer assistance with the multitude of tasks in the driver's cabin.…”
Section: Driver Distractionmentioning
confidence: 99%
“…Previous studies have demonstrated the impact of rear-seat passengers' activity on driver distraction [16,17], but this issue is amplified, in most ES situations, as the codriver, normally assisting in navigation, is often required to aid a patient and thus cannot offer assistance with the multitude of tasks in the driver's cabin.…”
Section: Driver Distractionmentioning
confidence: 99%
“…Thus, maintaining the flow and speed momentum could be a challenge in a real-life, non-deterministic road-traffic. In this case, additional support and provision of information could be employed in a timely manner and with minimal cognitive load requirements to the driver through a combinatory approach of AI / HUD [21,22].…”
Section: High Speed and Manoeuvringmentioning
confidence: 99%
“…The particular HUD system design employs the Augmented Reality (AR) element, which superimposes information related to the external environment to the gaming story [12]. By blending seamlessly, the two, the gaming software, embedded on the system, could adapt to the external environment landmarks and provide the younger population with informative, yet enjoyable gaming experience [3,5,6].…”
Section: System Design Requirementsmentioning
confidence: 99%
“…This paper presents an alternative solution that aims to attract younger passengers' attention for long periods of time, provide them with educational information and enable them to interact with the provided infotainment. This solution is based on an Augmented Reality (AR) Head-Up Display (HUD), which operates on the passenger side windows [2,3]. Notably the AR HUD technology enhances the user immersion and improves user's reaction time whilst offering positive usability experience [4,5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation